Pelatihan Manajemen Perdarahan Pertolongan Pada Anak untuk Kader Desa Rancawiru, Slawi, Kabupaten Tegal - Ratna Widhiastuti; Wisnu Widyantoro; Umi Salamah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Hemorrhage is one of the health issues that can be life-threatening, especially in children. This community service research aims to provide training and education to health cadres in the Rancawiru Village on the management of hemorrhage in children as the first response in handling emergencies. Interactive education methods are used to enhance the knowledge and skills of the cadres in managing hemorrhage in children. The results indicate an improvement in the knowledge and skills of the cadres, which is expected to enhance the prompt response to cases of hemorrhage in children in the community